Workload, staff composition, and sickness absence. Findings from employees in child care centers - Trude Gunnes; Nina Drange; Kjetil Telle (Statistics Norway, Research Department, 2018)
Persistently high workload may raise sickness absence with associated costs to firms and society. We proxy workload by the number of adults per child in Norwegian child care centers, but do not find that centers with many adults per child have lower sickness absence than other centers. However, we do find that more college-educated teachers per child are associated with lower sickness absence, whereas more assistants (with low or no education) per child are associated with higher sickness absence, suggesting that the observed variation in sickness absence at the center level is mainly driven by compositional differences of the employees rather than workload. The importance of compositional effects is supported by findings from individual fixed effects models and a regression discontinuity approach relying on results from municipal elections.
Keywords: I1; I2; 330; Workload; sickness absence; child care centers; teachers per child; education level